Fusobacterium nucleatum and colorectal cancer: From phenomenon to mechanism - Ou, Suwen; Wang, Hufei; Tao, Yangbao; Luo, Kangjia; Ye, Jinhua; Ran, Songlin; Guan, Zilong; Wang, Yuliuming; Hu, Hanqing; Huang, Rui (Frontiers in Cellular and Infection Microbiology, 2022)
Colorectal cancer(CRC) is the third most frequent malignant tumor. The gut microbiome acts as a vital component of CRC etiology. Fusobacterium nucleatum(Fn) is a key member of colorectal cancer-associated bacteria. But we lack a systematic and in-depth understanding on its role in CRC evolution. In this article, We reviewed the abundance changes and distribution of Fn in CRC occurrence and development, potential effect of Fn in the initiation of CRC, the source of intratumoral Fn and the cause of its tropism to CRC. In addition, We described the mechanism by which Fn promotes the malignant biological behavior of CRC, affects CRC response to therapy, and shapes the cancer-promoting immune microenvironment in great detail. Based on the relationship between Fn and CRC, we proposed strategies for CRC prevention and treatment, and discuss the feasibility and limitations of specific cases, to gain insights into further basic and clinical research in the future.